Exploration of the Molecular Mechanisms Underlying the Anti-Photoaging Effect of Limosilactobacillus fermentum XJC60 - Chen, Huizhen; Li, Ying; Xie, Xinqiang; Chen, Moutong; Xue, Liang; Wang, Juan; Ye, Qinghua; Wu, Shi; Yang, Runshi; Zhao, Hui; Zhang, Jumei; Ding, Yu; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Although lactic acid bacteria (LAB) were shown to be effective for preventing photoaging, the underlying molecular mechanisms have not been fully elucidated. Accordingly, we examined the anti-photoaging potential of 206 LAB isolates and discovered 32 strains with protective activities against UV-induced injury. All of these 32 LABs exhibited high levels of 2,2-diphenyl-picrylhydrazyl, as well as hydroxyl free radical scavenging ability (46.89–85.13% and 44.29–95.97%, respectively). Genome mining and metabonomic verification of the most effective strain, Limosilactobacillus fermentum XJC60, revealed that the anti-photoaging metabolite of LAB was nicotinamide (NAM; 18.50 mg/L in the cell-free serum of XJC60). Further analysis revealed that LAB-derived NAM could reduce reactive oxygen species levels by 70%, stabilize the mitochondrial membrane potential, and increase the NAD+/NADH ratio in UV-injured skin cells. Furthermore, LAB-derived NAM downregulated the transcript levels of matrix metalloproteinase (MMP)-1, MMP-3, interleukin (IL)-1β, IL-6, and IL-8 in skin cells. In vivo, XJC60 relieved imflammation and protected skin collagen fiber integrity in UV-injured Guinea pigs. Overall, our findings elucidate that LAB-derived NAM might protect skin from photoaging by stabilizing mitochondrial function, establishing a therotical foundation for the use of probiotics in the maintenance of skin health.